LONTO LEOK SEBAGAI POLITIK ELEKTORAL CALON KEPALA DESA KOMBO - Yoan Maureen Darianty Dara Odrada; Wawan Sobari; Muhtar Haboddin, Muhtar (Media Bina Ilmiah, 2024)
One of the democratic traditions born from the local cultural heritage of the Manggarai people is the lonto leok tradition. Literally, lonto leok means sitting in a circle to discuss or resolve a problem by prioritizing consensus. The lonto leok activity is carried out by the community wrapped in a series of traditional rituals and traditional expressions of the Manggarai people. Until now, lonto leok is still one of the most effective strategies in community political activities, especially in the 2022 Kombo village head election, which is being contested by three village head candidates. This research aims to see how the democratic process is based on local Lonto Leok culture and what factors influence voter behavior in the election of Kombo village head. The theory used in this research is local democracy and New institutionalism. In this research, qualitative research methods were used and the type of research was case study. This research shows the results that these three candidates use lonto leok as a forum to socialize themselves to the public and at the same time show that lonto leok is a manifestation of democracy which prioritizes the value of deliberation and consensus.The frenzy in the election of the Kombo Village Head cannot be separated from the role of local (political) actors and the existence of the lonto leok tradition as a cultural tool that connects various actors with various interests in them so as to produce joint decisions and decisions.In this research, the three village head candidates used lonto leok media as a means of socializing themselves in order to attract the sympathy of the village community in gaining votes in the Kombo village head election.